The Use of Eculizumab in Tacrolimus-Induced Thrombotic Microangiopathy - Jihad Ben Gabr MD; Hiba Bilal MD; Kanish Mirchia MD; Andras Perl MD, PhD (SAGE Publishing, 2020)
Drug-induced thrombotic microangiopathy (DITMA) is a secondary cause of thrombotic microangiopathy and a potentially fatal inflammatory disease. DITMA has been attributed to a variety of drugs, particularly chemotherapeutic and immunosuppressive agents. Prompt diagnosis is critical for survival and treatment necessitates withdrawal of the offending drug; however, many cases require further treatment including plasmapheresis, immunosuppression, and anticoagulation. In this article, we report a cutaneous biopsy-proven case of tacrolimus-induced DITMA, which was successfully treated with eculizumab after failing the conventional standard of care.